Apple confidential 2.0 : the definitive history of the world's most colorful company. - Linzmayer, Owen W., ....- (San Francisco : No Starch, 2004)
Examines the tumultuous history of America's best known Silicon Valley start-up - from its legendary founding more than 30 years ago, through a series of disastrous executive decisions, to its recent move into the music business.
Keywords: Ondernemingen